The Implementation of Portfolio Based Learning to Improve Junior High School Student Learning Outcomes in Civic About State Sovereignty Concept - Rinceu Anita (Jurnal Civicus, 2022)
This research analyzed the implementation of portofolio based learning models in improving learning outcomes of junior high school students on state sovereignty concept. Methods of research used in Classroom Action Research (CAR), consisted from three Step that is cycle 1, cycle 2, and cycle 3. The sample of this research was one class that consist of 20 Junior High School student in SMPN 2 Sukaraja. This research this conducted with give question about state sovereignty before learning based portfolio model applied. After that for meeting then in cycle 1 start applied learning-based portfolio model until cycle 3. Learning process in all cycles are measured with sheet observation, after that the observer gives reflection on the teacher for cycle improvement. Study results students are measured with give post-test. After applied learning model-based portfolio, the results study show that learning outcomes of student increased in each cycle. In cycle 3 results study whole student get value above KKM. The activities on the portfolio model by the teacher and students are carried out well. Research results this show that learning based portfolio model could use for increase results study student.